Variable and interactive effects of Sex, APOE ε4 and TREM2 on the deposition of tau in entorhinal and neocortical regions - Joseph Giorgio; Caroline Jonson; Yilin Wang; Jennifer S. Yokoyama; Jingshen Wang; William J. Jagust; On behalf of the Alzheimer’s Disease Neuroimaging Initiative (Nature Communications)
Abstract The canonical Alzheimer’s Disease (AD) pathological cascade posits that the accumulation of amyloid beta (Aβ) is the initiating event, accelerating the accumulation of tau in the entorhinal cortex (EC), which subsequently spreads into the neocortex. Here in a multi-cohort study (ADNI, A4, HABS-HD) of 1354 participants with multimodal imaging and genetic information we queried how genetic variation affects these stages of the AD cascade. We observed that females and APOE-ε4 homozygotes are more susceptible to the effects of Aβ on the primary accumulation of tau, with greater EC tau for a given level of Aβ. Furthermore, we observed for individuals who have rare risk variants in TREM2 and/or APOE-ε4 homozygotes there was a greater spread of primary tau from the EC into the neocortex. These findings offer insights into the function of sex, APOE and microglia in AD progression and have implications for determining personalised treatment with drugs targeting Aβ and tau.